Efficacy and safety of SGLT2 inhibitors in acute heart failure: a systematic review and meta-analysis of randomized controlled trials - Rahil, Ali Ibrahim; Bhavsar, Tirth; Fatima, Romman; Rajkumar, Aparajitha; Kumar, Joy; Majidan, Hanif Al; Gajjala, Namrata; Lefranc, Wodwentzky; Deeksha, Fnu; Lingegowda, Harshitha; Ehsan, Muhammad; Ur Rehman, Wajeeh; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAcute heart failure (AHF) is a serious medical condition with considerable morbidity and mortality ranging from 20%–30% within the first month following hospital admission. We aimed to evaluate the efficacy and safety of sodium-glucose cotransporter-2 (SGLT2) inhibitors administered within the first five days of hospitalization for AHF.MethodsWe utilized various electronic resources such as MEDLINE, Embase, and the Cochrane Library to retrieve relevant randomized controlled trials (RCTs). The meta-analysis was performed using Revman, where the risk ratio (RR) and mean difference (MD) with a 95% confidence interval (CI) were used for dichotomous and continuous variablesrespectively.ResultsA total of seven trials were included in this review. SGLT2 inhibitors were associated with decreased all-cause mortality (RR = 0.61, 95% CI = 0.40, 0.95; P = 0.03), worsening of HF (RR = 0.59, 95%CI = 0.36, 0.97;P = 0.04), and GFR (MD: 1.05, 95% CI = 0.68, 1.43; P < 0.00001) compared with the control group. There were no significant differences between the two groups regarding readmission for HF, cardiovascular mortality, AKI, hypoglycemia, hypotension, and diuretic efficiency. SGLT2 inhibitors were associated with improved KCCQ-CSS scores (MD: −3.82, 95% CI = −7.51, −0.13; P = 0.04).ConclusionSGLT2 inhibitors demonstrate overall clinical benefits and a favorable safety profile in acute heart failure, although their impact on readmission rates is limited. Further research is needed to refine patient selection and optimize treatment strategies.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024571563, PROSPERO (CRD42024571563).